A deletion of one nucleotide results in functional deficiency of apolipoprotein CII (apo CII Toronto). Issue 10 (October 1988) - Cox, D W; Wills, D E; Quan, F; Ray, P N
Abstract : Apolipoprotein CII Toronto is a mutant non-functional apo CII resulting in apo CII deficiency. A portion of the mutant apo CII gene was cloned into lambda gt10 and subclones were sequenced. A deletion of one base was found in the codon for amino acid Thr68, resulting in alteration of six amino acids and premature termination of the protein at amino acid 74.